Coupling of MAPbI3 microcrystals with conductive polyaniline for efficient visible-light-driven H2 evolution. Issue 1 (6th December 2021) - Li, Wenbo; Wang, Fang; Zhang, Zhengguo; Ma, Xiaohua; Min, Shixiong
Abstract : Coupling of MAPbI3 microcrystals with conductive PANI NWs leads to efficient photocatalytic H2 evolution under visible light. Abstract : Although the methylammonium lead iodide (MAPbI3 ) hybrid perovskite has shown great potential in photocatalytic H2 evolution, its performance is significantly suppressed due to the insufficient charge separation. Herein, a strongly coupled 3D/1D composite photocatalyst of MAPbI3 microcrystals with conductive polyaniline nanowires (PANI NWs) is developed for efficient photocatalytic H2 evolution in MAPbI3 -saturated HI aqueous solution under visible light irradiation. The most active MAPbI3 (100 mg)–PANI NW (7 mg) composite exhibits a H2 evolution rate of 38.8 μmol h −1, which is 29 times higher than that of pristine MAPbI3 . Spectroscopic and photoelectrochemical measurements reveal that the coupled PANI NWs can greatly improve the charge separation, thereby considerably enhancing the photocatalytic H2 evolution of the composite photocatalyst.